A Decision Support System for Selecting the Best Private Universities in Yogyakarta Using MARCOS Method - Nasyuha, Asyahri Hadi (Asosiasi Perguruan Tinggi Informatika dan Ilmu Komputer (APTIKOM) Provinsi Sumatera Utara, 2024)
Decision-making in higher education often involves evaluating multiple and sometimes conflicting criteria, particularly in regions such as Yogyakarta, Indonesia, which hosts more than one hundred private universities. Selecting the best institution is therefore a critical and complex task for students, parents, and policymakers. Traditional decision support system (DSS) methods such as SAW, TOPSIS, and AHP are widely applied but remain prone to sensitivity in weight assignment and rank reversal, which may compromise reliability. This study proposes the use of the MARCOS (Measurement of Alternatives and Ranking according to Compromise Solution) method, a recent multi-criteria decision-making (MCDM) technique introduced in 2019, to overcome these shortcomings. MARCOS simultaneously considers both ideal and anti-ideal solutions to achieve more stable rankings. A DSS model was developed and applied to five private universities in Yogyakarta UII, UMY, UAJY, USD, and UTDI evaluated across six criteria: accreditation, doctoral lecturers, research publications, facilities, tuition fees, and graduate employability. The results revealed that Universitas Islam Indonesia (UII) obtained the highest utility score (f(Ki)=0.7404 and ranked first, followed by Universitas Muhammadiyah Yogyakarta (0.6931), Universitas Atma Jaya Yogyakarta (0.6498), Universitas Sanata Dharma (0.6126), and Universitas Teknologi Digital Indonesia (0.5831). Sensitivity analysis further demonstrated that the ranking of UII remained unchanged across weight variations, confirming the robustness of MARCOS. Comparisons with TOPSIS also showed fewer rank reversals, reinforcing the stability of MARCOS in multi-criteria decision-making. This research contributes a novel application of MARCOS in higher education and offers stakeholders a transparent, objective, and data-driven tool for selecting the best private universities in Yogyakarta.